A virtual environment for learning computer coding using gamification and emotion recognition. Issue 8 (16th November 2020) - Zatarain Cabada, Ramón; Barrón Estrada, María Lucía; Ríos Félix, José Mario; Alor Hernández, Giner
ABSTRACT: Emotions play an important role in students learning to master complex intellectual activities such as computer programing. Emotions such as confusion, boredom and frustration in the student are important factors in determining whether the student will master the exercise of learning to program in the short and long term. Motivation also plays an important role in learning a programing language. However, it is extremely difficult to motivate students who find themselves in a negative emotional state. We developed an advanced learning environment that detects and responds to student emotions by using machine learning techniques, and incorporates modern motivation strategies by using gamification methods. We conducted two experiments; one to evaluate the acceptance of the learning system and a second one to evaluate the academic performance. The results of the experiments show that intention to use is dependent on perceived enjoyment but not on perceived usefulness and attitude toward the system. Also, better results were obtained in a post-test from students who used the learning system, compared with those who didn't use it.